Histological changes of liver tissue and serobiochemical relation in does with pregnancy ketosis - A.F.M. Azmi; A.A.A. Ghani; A.S. Saadan; A. Mokrish; K.S. Lai; M. Zamri-Saad; A.B. Zuki; H.A. Hassim (Jurnal Ilmu Ternak dan Veteriner, 2016)
Histological changes of liver in does with pregnancy ketosis were characterized. Twenty pregnant does at day 80 of pregnancy were used for this experiment. A total of 10 does were fed by grass (Napier) and goat concentrate with water ad libitum. Those 10 goats considered as healthy pregnant goat, and another 10 goats showing clinical and subclinical signs of ketosis considered as unhealthy pregnant does. Liver biopsies were performed when clinical signs appeared. Beta-Hydroxybutyrate (BHBA), free fatty acid (FFA), and glucose were dosed. Histological preparation revealed similar incidence and intensity of mild liver steatosis with lower cellular vacuolation in hepatocyte presence in healthy late pregnant does. Almost all of the pregnant does with ketosis state (n=8/10) had large amount of small lipid droplets in almost every hepatocyte over the whole liver acinus with higher number of cellular vacuolation, and related with higher BHBA and FFA levels while low in glucose level.